Disagreement and Uncertainty Among Experts About how to Respond to Marijuana Use in Patients on Long-term Opioids for Chronic Pain: Results of a Delphi Study. Issue 2 (8th August 2019) - Starrels, Joanna L; Young, Sarah R; Azari, Soraya S; Becker, William C; Jennifer Edelman, E; Liebschutz, Jane M; Pomeranz, Jamie; Roy, Payel; Saini, Shalini; Merlin, Jessica S
Abstract: Background: Marijuana use is common among patients on long-term opioid therapy (LTOT) for chronic pain, but there is a lack of evidence to guide clinicians' response. Objective: To generate expert consensus about responding to marijuana use among patients on LTOT. Design: Analysis from an online Delphi study. Setting/Subjects: Clinician experts in pain and opioid management across the United States. Methods: Participants generated management strategies in response to marijuana use without distinction between medical and nonmedical use, then rated the importance of each management strategy from 1 (not at all important) to 9 (extremely important). A priori rules for consensus were established, and disagreement was explored using cases. Thematic analysis of free-text responses examined factors that influenced participants' decision-making. Results: Of 42 participants, 64% were internal medicine physicians. There was consensus that it is not important to taper opioids as an initial response to marijuana use. There was disagreement about the importance of tapering opioids if there is a pattern of repeated marijuana use without clinical suspicion for a cannabis use disorder (CUD) and consensus that tapering is of uncertain importance if there is suspicion for CUD. Three themes influenced experts' perceptions of the importance of tapering: 1) benefits and harms of marijuana for the individual patient, 2) a spectrum of belief about the overall riskiness of marijuana use, and 3) variable state laws or practice policies. Conclusions: Experts disagree and are uncertain about the importance of opioid tapering for patients with marijuana use. Experts were influenced by patient factors, provider beliefs, and marijuana policy, highlighting the need for further research.